(3GdCMcGe GdcHQis - (3YHO GdMb Hf YHO GdQMef Hf YHO Gddg GdCROj GdETHjdj, CHh eMeO, GdeYQha H` GHf GdNQGW,J (B581 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO habfG Gddg hEjGc aEfi LeYJ ai gPG GdcJGH eJaQbkG ef MjK QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3jfJgi CKfGA (B" (3HGH ajef eGJ hYdjg UjGe (B" (3hBNQ eG ajg (B: (3eG YdeJg UGe TgQkG ddg EdG QeVGf hdG CaWQ cdg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B92s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs